Desafios da avaliação continuada em um curso de engenharia - João Batista Camargo Junior; Jorge Rady de Almeida Junior; Paulo Sérgio Cugnasca (EccoS – Revista Científica)
Considering the learning techniques applied most recently, it is important to consider the issue of what is the best way to assess students in a particular discipline. These learning techniques have as scope to provide a better student achievement, considering a process that relies on continuous feedback, i.e. without applying the concept of the intermediate and final exams. Thus, this paper contains a brief description of the main methods of continuous assessment currently implemented, followed by the compilation of some queries made to students after completion of an undergraduate discipline, which applied the continuous assessment technique. These results were obtained through a questionnaire distributed at the last day of class.